The relation between vitamin D, calcium, and phosphor in growth retardation of child with chronic kidney disease - Radwika Swastanti Wijaya; Ariani; Krisni Subandiyah (Pediatric Sciences Journal, 2022)
Background: Growth retardation was a complication in chronic kidney disease (CKD). It is a condition that a child can not achieve linear potential growth. Fifty percent of children with CKD will have a height below the third percentile. The causes of growth disorders in CKD are multifactorial. Electrolyte hemostasis (calcium and phosphorus) and lack of vitamin D play a role in growth in children with CKD. The aim of this study was to determine the relationship between growth problems in children with chronic kidney disease and the correlation with vitamin D, calcium, and phosphorus. Method: This study was a retrospective observational analytical study design. The research subjects were taken from medical records from Saiful Anwar General Hospital in Malang from January 1st to December 2019. 68 pediatric patients aged 2 – 18 years old were diagnosed with chronic kidney disease, divided into 2 groups (with growth retardation and normal stature). Data were analyzed using SPSS v.26 for windows. Results: There was significant correlation between low vitamin D levels and growth retardation (p = 0.005), and significant correlation between calcium levels (p = 0.026) and phosphor levels (p = 0.222) and the incidence of growth retardation. Levels of vitamin D, calcium, and phosphor have a positive correlation with growth retardation 0.427, 0.277, dan 0.300 (p<0.05). Path analysis found a significant direct relationship between vitamin D on growth retardation (β = 0.358, p = 0.002) and had a greater effect when compared to the indirect relationship between vitamin D and growth retardation mediated by calcium and phosphorus. Conclusion: there is a correlation between vitamin D, calcium, and phosphorus with growth retardation in children with chronic kidney disease.